Acid‐activated nonviral peptide vector for gene delivery. (6th November 2019) - Ji, Kun; Xiao, Yi; Zhang, Wei
Abstract : Nonviral vector–based gene therapy is a promising strategy for treating a myriad of diseases. Cell‐penetrating peptides are gaining increasing attention as vectors for nucleic acid delivery. However, most studies have focused more on the transfection efficiency of these vectors than on their specificity and toxicity. To obtain ideal vectors with high efficiency and safety, we constructed the vector stearyl‐TH by attaching a stearyl moiety to the N‐terminus of the acid‐activated cell penetrating peptide TH in this study. Under acidic conditions, stearyl‐TH could bind to and condense plasmids into nanoparticle complexes, which displayed significantly enhanced cellular uptake and transfection efficiencies. In contrast, stearyl‐TH lost the capacities of DNA binding and transfection at physiological pH. More importantly, stearyl‐TH and the complexes formed by stearyl‐TH and plasmids displayed no obvious toxicity at physiological pH. Consequently, the high transfection efficiency under acidic conditions and low toxicity make stearyl‐TH a potential nucleic acid delivery vector for gene therapy. Abstract : To obtain ideal vectors with high efficiency and safety, we constructed the vector stearyl‐TH by attaching a stearyl moiety to the N‐terminus of the acid‐activated cell penetrating peptide TH. At acidic pH, stearyl‐TH could condense plasmids into nanoparticle complexes, which displayed significantly enhanced cellular uptake and transfection efficiencies. In contrast, stearyl‐TH lost the capacities of DNA binding and transfection at physiological pH.